Occupational Exposure to Formaldehyde and Genetic Damage in the Peripheral Blood Lymphocytes of Plywood Workers. Issue 4 (6th February 2014) - Lin, Dafeng; Guo, Yaojing; Yi, Jihu; Kuang, Dan; Li, Xiaohai; Deng, Huaxin; Huang, Kun; Guan, Lei; He, Yunfeng; Zhang, Xiao; Hu, Die; Zhang, Zhihu; et al.
Abstract : Occupational Exposure to Formaldehyde and Genetic Damage in the Peripheral Blood Lymphocytes of Plywood Workers: Dafeng LIN, et al . Institute of Occupational Medicine and the Ministry of Education Key Lab of Environment and Health, School of Public Health, Tongji Medical College, Huazhong University of Science and Technology, China— Objectives: We sought to clarify the association of occupational formaldehyde exposure with DNA strand breaks, chromosome damage and DNA‐protein crosslinks (DPCs) in the peripheral blood (PB) lymphocytes of plywood workers. Methods: We determined Olive tail moment (OTM) values, micronucleus (MN) frequencies and DPC rates of the PB lymphocytes in 178 workers divided into control and lower and higher exposure groups according to their current formaldehyde exposure levels and examined the association of each end point with formaldehyde exposure levels and with the number of work years. We also examined each end point in an additional 62 workers before and after an 8‐hour formaldehyde exposure for validating the association. Results: OTM values increased significantly in the two exposure groups compared with those in the control group ( p <0.05 for both) and were associated with increasing formaldehyde exposure levels =0.002), while MN frequencies increased with ( p trend increasing numbers of work years ( p <0.001). The trend dynamic study showed that OTM values and DPC rates increased after an 8‐hour formaldehyde exposure compared with those before the exposure ( p <0.001, p =0.019, respectively), that, in a dose‐dependent manner, OTM values were associated with formaldehyde exposure levels during work hours ( p =0.005) and that MN frequencies before and after the 8‐hour work exposure were associated with numbers of work years ( p =0.029, p <0.001, respectively). Conclusions: We found a dose‐response relationship between the current formaldehyde exposure levels and DNA strand breaks and between duration of exposure and chromosome damage in the PB lymphocytes of plywood workers.